Morphology of the female genital ducts of the blue land crab Cardisoma guanhumi (Crustacea: Brachyura: Gecarcinidae) - de Souza, Leonardo P. [UNESP]; Silva, José R.F.; Araujo, Andréa M. [UNESP]; Camargo-Mathias, Maria I. [UNESP] (Wiley, 2013)
This is a histological and histochemical analysis of the terminal portion of the female reproductive system and genital ducts of the blue land crab (Cardisoma guanhumi). Animals were collected in the Jaguaribe estuary (Ceará, Brazil) and dissected. Genital duct fragments were fixed and submitted to different staining techniques. The female reproductive system consists of a pair of ovaries and a pair of genital ducts. In the mid-posterior portion of each lobe, the ovaries communicate with the genital ducts, which are subdivided into oviduct, spermatheca, vagina, and gonopore. Histologically, the spermatheca of C. guanhumi is composed of columnar secretory epithelium and is divided into a dorsal zone and a ventral zone, the latter covered internally by a cuticle layer. Both zones are enveloped by a thin layer of loose connective tissue. Histological cross sections revealed the vagina to be concave, a pattern considered phylogenetically more advanced than the simple, tubular form. Our findings suggest fertilization is internal, favoring sperm from the most recent copulation. © 2012 The Authors. Acta Zoologica © 2012 The Royal Swedish Academy of Sciences.
Keywords: Reproduction; Spermatheca; Thoracotremata; copulation; crab; cuticle; fertilization (reproduction); histology; morphology; oviposition; phylogenetics; reproductive strategy; secondary sexual characteristics; secretion; sperm; Brazil; Ceara; Animalia; Brachyura; Cardisoma carnifex; Cardisoma guanhumi; Crustacea; Decapoda (Crustacea); Gecarcinidae